2010
DOI: 10.1007/s10531-010-9852-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-specific niche partitioning obscures the importance of fine-scale habitat data in species distribution models

Abstract: Geographic information systems (GIS) allow researchers to make cost-effective, spatially explicit predictions of species' distributions across broad geographic areas. However, there has been little research on whether using fine-scale habitat data collected in the field could produce more robust models of species' distributions. Here we used radiotelemetry data collected on a declining species, the North American wood turtle (Glyptemys insculpta), to test whether fine-scale habitat variables were better predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…Using the GPS-telemetry data at the daily time scale, we found that females moved significantly greater cumulative distances per day than males during July, August, and September. Estimates for both sexes were substantially greater than those derived from conventional radio-telemetry tracking studies of Wood Turtles (Arvisais et al 2002;Tingley et al 2010). The differences in the daily distance moved may be due to difference in broader movement patterns and habitat use.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Using the GPS-telemetry data at the daily time scale, we found that females moved significantly greater cumulative distances per day than males during July, August, and September. Estimates for both sexes were substantially greater than those derived from conventional radio-telemetry tracking studies of Wood Turtles (Arvisais et al 2002;Tingley et al 2010). The differences in the daily distance moved may be due to difference in broader movement patterns and habitat use.…”
Section: Discussionmentioning
confidence: 60%
“…This difference reveals that Wood Turtles move considerable more than previous radio-telemetry studies have estimated (e.g. Arvisais et al 2002;Tingley et al 2010) and is likely because the radio-telemetry data provides an estimate of the straight lines distance moved between locations 2-3 days apart whereas the GPS-telemetry data provides a more refined estimate of the actual movement trajectory. A more refined estimate of movement provides a better measure of actual distance moved and the habitats the individual moved through.…”
Section: Discussionmentioning
confidence: 72%
“…Levinsky et al (2007) recognize the limitations of bioclimatic models, although these are useful tools that provide a means of understanding the geographical distribution of the species in the present and future (Téllez-Valdés et al, 2006;Iverson and McKenzie, 2013). They also represent an option to plan the distribution of geographical areas for the conservation of biodiversity (Irfan-Ullah et al, 2007;Tingley et al, 2010).…”
Section: Conservation Measuresmentioning
confidence: 99%
“…, Tingley et al. ). However, we also included covariates based on ground observations and aerial photographs, so that the lack of explanatory ability of most finer‐scale habitat covariates cannot be attributed solely to the methodology used to generate them.…”
Section: Discussionmentioning
confidence: 99%
“…Work with the semiaquatic painted turtle (Chrysemys picta) found that landscape context in the form of distance to nearest wetlands was correlated with habitat use (Bowne et al 2006, Cosentino et al 2010, but other features such as the amount of forest or road proximity were not (Bowne et al 2006, Attum et al 2008. A possible issue in identifying finer-scale patterns of habitat associations is the use of GIS-generated variables, which may not detect habitat characteristics relevant to the turtles (Compton et al 2002, Tingley et al 2010). However, we also included covariates based on ground observations and aerial photographs, so that the lack of explanatory ability of most finerscale habitat covariates cannot be attributed solely to the methodology used to generate them.…”
Section: Discussionmentioning
confidence: 99%